ANALYZING THE INFLUENCE OF INTEREST RATES ON MONEY DEMAND ACCORDING TO KEYNESIAN THEORY - Aloysius Hari Kristianto (Department of Management - Institut Shanti Bhuana, 2019)
The purpose of this research is to analyze the factors that influence money demand which are characterized by the amount of money currency (M1) in Indonesia, one of which is interest rates. The model of observation analysis used in this study is OLS (Ordinary Least Square), as a whole the tests performed are by linear constraint tests, statistical tests and classic assumption tests. In this model, the variable domestic interest rates in Indonesia are used as explanatory components. From these variables examined whether it influences the demand for money (the velocity of money) M1 or not.The results obtained from this study are that domestic interest rates have a negative and significant influence on the demand for money in Indonesia, these results are consistent with Keynesian theory, that interest rates increase, the demand for money for the cash balance will decrease.